The deadlines for paying social security contributions - Wantoch-Rekowski, Jacek; Kwaśniewski, Robert; Wilmanowicz, Martyna (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2018)
Social security contributions are to be paid according to statutory deadlines. Failure to pay on time results in various consequences for the payer. First of all, according to Article 23 Sec. 1 of the law relating to the social security system, for unpaid contributions the payer must pay statutory interest. ZUS (the Polish Social Security Institution) may also apply a sanction in the form of imposing an additional fee. However, statutory deadlines may be modified – e.g., on the basis of Article 12 Sec. 5 of the Tax Ordinance or as a result of postponing the date of payment of contributions. A contentious issue, which is also analysed by the authors, is whether the repayment of overdue contributions in instalments causes the statutory deadline for their payment to be extended – until the date specified in the instalment agreement
Keywords: deadlines; social insurance contributions; facilitations in the payment of contributions